2018
DOI: 10.1016/j.dib.2018.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Data on heavy metal concentration in common carp fish consumed in Shiraz, Iran

Abstract: Food contamination by heavy metals can lead to the accumulation of these elements in the body of consumers and the contraction of diseases. Accordingly, heavy metal concentration in common carp fishes consumed in Shiraz, Iran was determined in the present study. The mean concentrations of Pb, Cd, Zn, and Cu were 0.23, 0.07, 0.47, and 0.59 mg/kg (dry weight), respectively. The average concentration of heavy metals in the muscle of common carps consumed in Shiraz was less than the permissible standard of the WHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The levels of Ag, Al and As were very similar to those reported from Tehran subjects (Rafiee et al, 2020), while concentrations of As in this study were higher than those reported in Portugal (Coelho et al, 2014), Greece (Sazakli & Leotsinidis, (Varrica et al, 2014). Thus, exposure to As in Iran appears to be associated with drinking water and dietary intake (Alamdar et al, 2019;Derakhshan et al, 2018;Rahmdel et al, 2018;Torghabeh et al, 2019). Concentrations of Ni are higher than those reported in Portugal, Greece and Italy (Coelho et al, 2013;Sazakli & Leotsinidis, 2017a;Varrica et al, 2014), although lower than concentrations reported in Taiyuan (China) (Zhu et al, 2018).…”
Section: Concentrations Of Metals and Metalloids In Hair Samplessupporting
confidence: 83%
See 1 more Smart Citation
“…The levels of Ag, Al and As were very similar to those reported from Tehran subjects (Rafiee et al, 2020), while concentrations of As in this study were higher than those reported in Portugal (Coelho et al, 2014), Greece (Sazakli & Leotsinidis, (Varrica et al, 2014). Thus, exposure to As in Iran appears to be associated with drinking water and dietary intake (Alamdar et al, 2019;Derakhshan et al, 2018;Rahmdel et al, 2018;Torghabeh et al, 2019). Concentrations of Ni are higher than those reported in Portugal, Greece and Italy (Coelho et al, 2013;Sazakli & Leotsinidis, 2017a;Varrica et al, 2014), although lower than concentrations reported in Taiyuan (China) (Zhu et al, 2018).…”
Section: Concentrations Of Metals and Metalloids In Hair Samplessupporting
confidence: 83%
“…Zn exposure could be attributed to males' use of health supplements (Rafiee et al, 2020). Exposure to Zn through inhalation of PM 10 (Parvizimehr et al, 2020) and re-suspended soil particles (Jahandari, 2020;Keshavarzi et al, 2015;Moghtaderi et al, 2020;Moghtaderi et al, 2019;Torghabeh et al, 2019) cannot be ignored, as well as from dietary intake (Ahmadi & Ziarati, 2015;Derakhshan et al, 2018;Rahmdel et al, 2018;Sepehri et al, 2018). The intake of Fe could be attributed to the use of health supplements, inhalation of particulate matter or dietary intake of kebab and grilled sheep's liver rich in iron and popular with males (Rafiee et al, 2020).…”
Section: Concentrations Of Metals and Metalloids In Hair Samplesmentioning
confidence: 99%
“…For instance, a study in China in 2014 showed that 19.4% of arable land across the country was contaminated by heavy metals 15 . The sources of TEs in soils include natural processes (volcanic eruptions, sea-salt sprays, forest fires, rock weathering, biogenic activities and wind-borne soil particulate matters) or human activities (mineral resource development, metal ores processing and smelting, chemical production, factory waste and wastewater irrigation) [16][17][18][19] . When high levels of TEs enter the soil environment, they destroy the structure and function of the environment and gradually deteriorate the soil quality and decrease the soil productivity and consequently affect human wellbeing via the food chain [20][21][22][23] .…”
mentioning
confidence: 99%
“…66/2003, and European Commission Regulation EC No. 1881/2006, the established limit for Hg is 0.5 mg/kg [55].…”
Section: Methodsmentioning
confidence: 99%